Storm warning [large type] - Goddard, Elizabeth (Hidden Bay, 2025)
"Haunted by a half-forgotten past, former army photographer Remi Grant is working at an isolated storm-watching lodge on the rocky Washington coast when she receives a mysterious puzzle piece. The puzzle piece may be the catalyst to unlock a disturbing incident she struggles to remember--the event that sent her into hiding. But with heavy storms rolling in, she has to focus on the present, not get caught up in the past. When a mysterious man at the lodge saves her life--twice--Remi becomes suspicious and confronts him. After a catastrophic event in his own life, former military pilot Hawk Beckett is trying to get some perspective at the suggestion of his former commanding officer. Faced with the fiercest storm to hit the coast in a decade, Remi and Hawk are forced into survival mode. But they're not alone at the lodge. Someone doesn't want Remi to remember what happened--and they will stop at nothing to see her dead."--